2011
DOI: 10.1111/j.1755-0998.2011.03015.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of microsatellite markers and genotyping performances using feathers and buccal swabs for the Ivory gull (Pagophila eburnea)

Abstract: We report 22 new polymorphic microsatellites for the Ivory gull (Pagophila eburnea), and we describe how they can be efficiently co-amplified using multiplexed polymerase chain reactions. In addition, we report DNA concentration, amplification success, rates of genotyping errors and the number of genotyping repetitions required to obtain reliable data with three types of noninvasive or nondestructive samples: shed feathers collected in colonies, feathers plucked from living individuals and buccal swabs. In two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…In comparison with a previous non-invasive study using ivory gull (Pagophila eburnea) feather samples (Yannic et al 2011), our newly developed marker set showed a higher amplification success rate (96.2% on average vs 93% in Yannic et al 2011; P < 0.05, Wilcoxon rank sum test) and similar ADO (6.43 vs 7.60; P = 0.32, Wilcoxon rank sum test) for molted feathers. For the plucked feathers, our marker set showed significantly lower ADO (0.28 vs 0.95; P < 0.01, Wilcoxon rank sum test) and a comparable amplification success rate (98.4% vs 99.57%).…”
Section: Discussionmentioning
confidence: 51%
“…In comparison with a previous non-invasive study using ivory gull (Pagophila eburnea) feather samples (Yannic et al 2011), our newly developed marker set showed a higher amplification success rate (96.2% on average vs 93% in Yannic et al 2011; P < 0.05, Wilcoxon rank sum test) and similar ADO (6.43 vs 7.60; P = 0.32, Wilcoxon rank sum test) for molted feathers. For the plucked feathers, our marker set showed significantly lower ADO (0.28 vs 0.95; P < 0.01, Wilcoxon rank sum test) and a comparable amplification success rate (98.4% vs 99.57%).…”
Section: Discussionmentioning
confidence: 51%
“…Buccal swabs are now regularly used for population genetics in a number of species: amphibians (Pidancier et al 2003;Broquet et al 2007a;Gallardo et al 2012), fish (Reid et al 2012) and mammals (Corthals et al 2015). Buccal swabs have lately been used in bird studies (e.g., Bush et al 2005;Handel et al 2006;Brubaker et al 2011;Yannic et al 2011), and a few studies have demonstrated the reliability of this sampling method for bird sex identification (Arima and Ohnishi 2006;Handel et al 2006;Wellbrock et al 2012;Dawson et al 2015). Finally, a strictly noninvasive approach would be to sex birds using DNA extracted from shed feathers.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a strictly noninvasive approach would be to sex birds using DNA extracted from shed feathers. Shed feathers yield DNA that is both less concentrated and more degraded (e.g., Yannic et al 2011), and its applicability for sexing has yet to be assessed (but see Hogan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…; Yannic et al . ) and amphibians (Prunier et al . ), swabbing for DNA proved to be an extremely useful technique in worm pipefish.…”
Section: Discussionmentioning
confidence: 99%